Remote sensing-based identification and mapping of salinised irrigated land between Upington and Keimoes along the lower Orange River, South Africa - Mashimbye, Zama Eric (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2005.